2009
DOI: 10.1111/j.1365-2621.2008.01783.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of osmotic dehydration on the drying kinetics and quality of cashew apple

Abstract: The effect of different osmotic pretreatments on cashew apple drying kinetics and product quality were investigated. The osmotic pretreatment was carried out in an incubator at constant temperature and agitation. The drying process was conducted in a fixed bed dryer at different temperatures and constant air velocity. Experimental data were fitted successfully using the Page and the two-term exponential models for dried fresh and pretreated fruit, respectively. It was found that drying rates of osmosed fruits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 26 publications
2
34
0
3
Order By: Relevance
“…The agreement between the prediction and measured values of Page model is good and this shows the suitability of the model, which has been used to accurately simulate the drying curves of papaya [14], kiwi [48], cashew apple [4], litchi [23], among others.…”
Section: Drying Characteristicsmentioning
confidence: 79%
See 1 more Smart Citation
“…The agreement between the prediction and measured values of Page model is good and this shows the suitability of the model, which has been used to accurately simulate the drying curves of papaya [14], kiwi [48], cashew apple [4], litchi [23], among others.…”
Section: Drying Characteristicsmentioning
confidence: 79%
“…Osmotic dehydration is the most reported pretreatment used prior to air-drying [2,4,18,29,39], and it can be used to improve nutritional, sensorial and functional properties of food without changing the integrity of the foods [33,55,56]. However, among emerging new technologies, ultrasonically assisted osmotic dehydration is very promising because the process can be carried out at low temperatures, which reduces the probability of food degradation [31] and permits the removal of moisture content from solids without producing a liquid phase change [18].…”
Section: Introductionmentioning
confidence: 99%
“…A evaporação da água dentro do alimento é influenciada por diversos fenômenos, como: capilaridade, ligação físico-química da água às substâncias sólidas presentes no alimento, migração de solutos, deformação do produto, entre outros; note-se que tais fenômenos oferecem grande resistência (BENDLIN, 2003). Pena et al (2008), na secagem da fibra residual do maracujá, e Azoubel et al (2009), na secagem de caju com e sem pré-tratamento osmótico, observaram também taxas de secagem decrescentes.…”
Section: Ajuste Matemático Das Cinéticas De Secagemunclassified
“…For example, in cashew drying and the residual passion fruit fiber, it was also observed a decreasing drying rate (Pena et al, 2008;Azoubel et al, 2009). Dliveira et al (2014) have obtained a drying curve similar to that found in the present study, when evaluating the drying curve of dry Jambu, in the oven at 45 °C.…”
Section: Drying Curvementioning
confidence: 99%